(untitled) (Al-Aasar, 2026)
Climate change is currently global crisis determined primarily by human activities. This article examines climate change through an Islamic ethical lens by synthesizing Qur’anic principles and Prophetic teachings with contemporary environmental issues.The Qur’an does not directly talk about environmental problems like climate change. However, it is an eternal book that guides humanity for every domain of life. Although climate change is not mentioned by name, the Qur’an provides important principles such as human responsibility (stewardship), balance in nature (mizan), avoiding waste (israf), and preventing corruption (fasad). These principles can be applied to environmental ethics and can guide us toward healthy living. The Sunnah reinforces these values through the principle of “no harm” (la darar wa la dirar), encouragement of tree planting, compassion towards animals, and conservation of natural resources such as water. Together, the Qur’anic and Prophetic perspectives provide a moral foundation that complements understanding and motivates responsible environmental behavior, making Islamic teachings a relevant and constructive contribution to global climate discourse.